2017
DOI: 10.1002/ffj.3415
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective syntheses and sensory properties of 2‐Alken‐4‐olides

Abstract: A series of optically active 2‐alken‐4‐olides of C6‐C11 were obtained with 89–97% enantiomeric excess (ee) values by the Sharpless asymmetric dihydroxylation (AD) of methyl (E)‐3‐alkenoates, followed by elimination via mesylates. The odor features and thresholds of the enantiomers were determined by means of chiral gas chromatography‐olfactory (GC‐O). The data revealed that all the samples exhibited stereospecific differences in sensory properties. Both enantiomers of 2‐octen‐4‐olide had the two lowest odour t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In accordance with Dai's and Liu's procedure, sensory panels were determined. 38 There were five judges, aged 23-29, who were healthy, non-smokers. Two men and three women made up the panel.…”
Section: Sensory Panelmentioning
confidence: 99%
“…In accordance with Dai's and Liu's procedure, sensory panels were determined. 38 There were five judges, aged 23-29, who were healthy, non-smokers. Two men and three women made up the panel.…”
Section: Sensory Panelmentioning
confidence: 99%
“…Sensory panels were determined according to the procedure described by Dai and Liu. 33 The panel consisted of ten healthy, nonsmoking judges, four men and six women, aged 23-29 years old. All the panel members belonged to the Henan Agricultural University.…”
Section: Sensory Panelmentioning
confidence: 99%
“…In addition, a series of optically active 2‐alken‐4‐olides of C 6 –C 11 were also prepared by the Sharpless asymmetric dihydroxylation of methyl ( E )‐3‐alkenoates, followed by elimination via mesylates in our laboratory in order to examine the odour properties. The odour evaluation revealed that all of the samples exhibited stereospecific differences in sensory properties; however, the application of these optically active 2‐alken‐4‐olides is impossible for the time being, as those chiral oxidants are too expensive for industrial production. Like the saturated γ ‐lactones, the racemic mixtures still predominate over the enantiomers in the market, even with these well‐known stereospecific differences in sensory properties.…”
Section: Introductionmentioning
confidence: 99%